Low serum omentin levels in the elderly population with Type 2 diabetes and polyneuropathy. Issue 11 (11th June 2015) - Herder, C.; Bongaerts, B. W. C.; Ouwens, D. M.; Rathmann, W.; Heier, M.; Carstensen‐Kirberg, M.; Koenig, W.; Thorand, B.; Roden, M.; Meisinger, C.; Ziegler, D.; for the KORA Study Group
Abstract Aims To investigate the hypothesis that high serum levels of omentin, an adipokine with anti‐inflammatory, insulin‐sensitizing and cardioprotective properties, may be related to a lower risk of diabetic sensorimotor polyneuropathy. Methods The association between serum omentin level and polyneuropathy was estimated in people aged 61–82 years with Type 2 diabetes (47 with and 168 without polyneuropathy) from the population‐based KORA F4 study. The presence of clinical diabetic sensorimotor polyneuropathy was defined as bilateral impairment of foot vibration perception and/or foot pressure sensation. Omentin levels were determined by enzyme‐linked immunosorbent assay. Results Serum omentin level was inversely associated with polyneuropathy after adjustment for age, sex, height, waist circumference, hypertension, total cholesterol, smoking, alcohol intake and physical activity [odds ratio 0.45 (95% CI 0.21–0.98); P = 0.043]. Although omentin was positively correlated with adiponectin (r = 0.55, P < 0.0001) and inversely with tumour necrosis factor‐α (r = ‐0.30, P = 0.019), additional adjustment for adiponectin and tumour necrosis factor‐α had little impact on the association. Conclusions Serum levels of omentin are reduced in people with Type 2 diabetes and diabetic sensorimotor polyneuropathy, independently of established risk factors of polyneuropathy. This association is only partially explained by biomarkers of subclinical inflammation.